If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-1)-5x-4)=-9
We move all terms to the left:
3(2x-1)-5x-4)-(-9)=0
We add all the numbers together, and all the variables
-5x+3(2x-1)=0
We multiply parentheses
-5x+6x-3=0
We add all the numbers together, and all the variables
x-3=0
We move all terms containing x to the left, all other terms to the right
x=3
| x^2-x-6=(x-2)(x+3) | | 3/4x+2=-1/4x+6 | | 5x–4(x–6)=–11 | | 2x4=6 | | -x-17=-11 | | 5(y-6)+39=3(15-y)+4y | | 185-u=43 | | 230=42-w | | -v+29=255 | | -3/4x-7=1 | | x/3.2-8=6 | | x/2.9+3=13 | | 751=28a-59 | | -x-36=3(2x-5) | | 3(4x+5)=3 | | 2(2x+5)=2x+22 | | 6x+4=154 | | 2(3x-4)=3x-5 | | -22=2(x-4) | | 4y-235=-200 | | -2x+28=2x+32 | | 2(2x-3)=-3x+22 | | 3(5x-1)=-2x-37 | | 3x-21=33-2x | | 5(3x-1)=3x+31 | | 2(3x+4)=2x+28 | | 2(x+2)-6=3x-5 | | 4(2x+2)=3x+33 | | 2(2x-3)-8=-3x+7 | | 8y^2+12(√2)y=306 | | 5(x+1)=-3x+37 | | 8y^2+12*(2^.5)y=306 |